Cellular Ti6Al4V with carbon nanotube-like structures fabricated by selective electron beam melting. Issue 6 (20th October 2014) - Quan, Yujie; Drescher, Philipp; Zhang, Faming; Burkel, Eberhard; Seitz, Hermann
Abstract : Purpose: – The purpose of this paper is to fabricate cellular Ti6Al4V with carbon nanotube (CNT)-like structures by selective electron beam melting and study the resultant mechanical properties based on each respective geometry to provide fundamental information for optimizing molecular architectures and predicting the mechanical properties of cellular solids. Design/methodology/approach: – Cellular Ti6Al4V with CNT-like zigzag and armchair structures are fabricated by selected electron beam melting. The microstructures and mechanical properties of these samples are evaluated utilizing scanning electron microscopy, synchrotron radiation X-ray and compressive tests. Findings: – The mechanical properties of the cellular solids depend on the geometry of strut architectures. The armchair-structured Ti6Al4V samples exhibit Young's modulus from 501.10 to 707.60 MPa and compressive strength from 8.73 to 13.45 MPa. The zigzag structured samples demonstrate Young's modulus from 548.19 to 829.58 MPa and compressive strength from 9.32 to 16.21 MPa. The results suggest that the zigzag structure of the Ti6Al4V cellular solids can achieve improved mechanical properties and the mechanism for the enhanced mechanical properties in the zigzag structures was revealed. Originality/value: – The results provide an innovative example for modulating the mechanical properties of cellular titanium by adjusting the unit cell geometry. The Ti6Al4V cellular solids with single-walled CNT-like structures could be used as light-weight construction components or filters in industries. The Ti6Al4V with multiwalled CNT-like structures could be used as new scaffolds for biomedical applications.